Integrated weed management in potato at Munshigonj - Khan, ASA; Hossain, MA; Mahmud, AA; Howlader, MIA; Rahman, MA (Bangladesh Journal of Agricultural Research, 2009)
A field experiment was carried out at the research farm of Tuber Crops Research Sub-station, Munshigonj of Bangladesh Agricultural Research Institute (BARI) during rabi seasons of 2005-06 and 2006-07 to find out the effective and economical integrated weed control method in potato. Chenopodium album and Amaranthus viridis were the major weed species in potato field. Mulch (water hyacinth) along with herbicide application (Ronstar 25 EC @ 1 ml/L water) at 7 days after planting (DAP) was found most effective in controlling weed population (94 to 95%) upto 30 days of planting than that employed by only mulch (45 to 53%). The weeds were found to reduce tuber yield to the extent of 43 percent. Mulching plus herbicide spraying at 7 DAP followed by one time uprooting of weeds by hand at 25 DAP produced the highest tuber yield of 23.39 t/ha in 2005-06 and 29.58 t/ha in 2006-07 and it was most effective in controlling weeds as compared to unweeded and mulched plots. The highest net returns (Tk. 116141/ha in 2005-06 and Tk. 205646/ha in 2006-07) and maximum benefit cost ratio of 2.64 and 3.28 were noted with mulching by water hyacinth + herbicide application at 7 DAP + one time weed uprooting by hand at 25 DAP. Key Words: Weed management, mulching, herbicide, potato tuber yield. doi: 10.3329/bjar.v33i4.2309 Bangladesh J. Agril. Res. 33(4) : 647-654, December 2008